2010
DOI: 10.3816/clml.2010.n.078
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Patients With IgD and IgM Multiple Myeloma Undergoing Autologous Hematopoietic Stem Cell Transplantation: A Retrospective CIBMTR Study

Abstract: Introduction Immunoglobulin D (IgD) and IgM multiple myeloma represent uncommon immunoglobulin isotypes, accounting for 2% and 0.5% of cases, respectively. Limited information is available regarding the prognosis of these isotypes, but they have been considered to have a more aggressive course than the more common immunoglobulin G (IgG) and IgA isotypes. In particular, the outcome after autologous hematopoietic stem cell transplantation (auto-HCT) has not been well defined. Patients and Methods Using the Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 18 publications
3
27
1
1
Order By: Relevance
“…In this study, the median overall OS (37.7 months) was remarkably improved, possibly because of the use of novel agents as induction therapy, relative to the median OS (12 months) reported in our previously conducted study [11]; however, these outcomes are still shorter than those reported in studies conducted in Western countries [3, 10, 12, 13, 17, 18]. …”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In this study, the median overall OS (37.7 months) was remarkably improved, possibly because of the use of novel agents as induction therapy, relative to the median OS (12 months) reported in our previously conducted study [11]; however, these outcomes are still shorter than those reported in studies conducted in Western countries [3, 10, 12, 13, 17, 18]. …”
Section: Discussioncontrasting
confidence: 51%
“…Our previously conducted retrospective study reported poorer outcomes in cases of IgD MM, relative to the other MM isotypes, after ASCT [11]. In contrast, 2 other reports suggested that similar outcomes were observed after ASCT in cases of IgD myeloma and common isotypes of MM [12, 13]. …”
Section: Introductionmentioning
confidence: 78%
“…Results are contradictory [9-12]. In a study from the Centre for Blood and Marrow Research (CIBMTR) in 36 subjects my colleagues and I found similar outcomes to persons with IgG and IgA plasma cell myeloma [13]. However, another study in 17 subjects reported worse outcomes [14].…”
mentioning
confidence: 87%
“…There have been a number of recent reports of the outcome of autologous transplantation for the rare myelomas (IgD, IgE, IgM, and nonsecretory myeloma [NS]) [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%